Preparation of GPP Chips Based on Screen Printing Method - Changpo XU; Dou LI (机车电传动)
Glassivation passivation parts (GPP) is a general term for glass passivation devices. Based on the ordinary silicon rectifier diffusion sheet, a layer of glass is burned around the P/N junction surface of the pipe core to be divided. The glass has a good combination characteristic with monocrystalline silicon, which can make the P/N junction obtain the best protection and improve the stability of the device. By completing the industrial production of screen printing through experiments, the paste of screen printing protective layer, screen printing glass layer slurry technology and the drying process of screen printing glass layer were determined,and the industrial production capacity of 250 000 GPP wafers per month by screen printing was realized.